Growing Understanding of Subduction Dynamics Indicates Need to Rethink Seismic Hazards. (26th March 2013) - Morra, Gabriele; Geller, Robert J.; Grilli, Stephan T.; Karato, Shun‐ichiro; King, Scott; Lee, Sang‐Mook; Tackley, Paul; Yuen, David
Abstract : Tsunamigenic megathrust earthquakes, like the 2004 Sumatra‐Andaman and 2011 Tohoku events, are the most dramatic consequences of subduction dynamics. The classical view is that megathrusts release elastic energy due to the rupture of a fault with a width of tens of kilometers in the down‐dip direction and a length of hundreds to a thousand kilometers along the trench. However, recent research, particularly work on the Tohoku event, has suggested that the generation of huge tsunamis may require the release of gravitational energy as well as elastic energy [ George et al ., 2011]. Our growing understanding of the role of gravitational energy in generating tsunamis following megathrust earthquakes points to the need to reevaluate earthquake and tsunami hazard assessments.